THE EFFECT OF HUMIC ACID DOSAGE ON THE GROWTH AND YIELD OF BITTER MELON PLANTS (Momordica charantia L.) - Widari, Dessy Nur (International Journal of Multidisciplinary Research and Literature, 2024)
Bitter melon plant (Momordica charantia L.) is a plant originating from Asia and cultivated as a vegetable taken for fruit. Bitter melon plants can be cultivated both in lowlands and plains with sufficient light intensity. Knowing the optimal dose of humic acid for the growth and yield of bitter melon plants (Momordica charantia L.). The research design used was a single-factor RAK (Group Random Design). The hypothesis about the effect of treatment is tested through the F test, if the F test is real (significant) then the calculation is continued with the 5% BNJ test. The treatment of humic acids in accordance with the treatment used is A0 (without humic acids), A1 humic acid 1 kg / Ha (0.04 g / plant), A2 humic acid 3 kg / Ha (0.12 g / plant), A3 humic acid 5 kg / Ha (0.20 g / plant), A4 humic acid 7 kg / Ha (0.28 g / plant). The results of the study found that the use of humic acids that have a high effect on bitter melon plants is the use of humic acid doses with 5 kg / Ha and 7 kg / Ha found in the treatment (A3) and (A4). The use of humic acid in the vegetative period of plants is best to use humic acid 7kg / Ha, while in the generative period bitter melon plants use a very influential dose of humic acid by using a dose of 7 kg / Ha